The Spirit in 1 Corinthians: Spiritual Formation and Giftedness - Adewuya, J. Ayodeji (Pneuma, 2021)
Abstract The Holy Spirit plays a significant role in 1 Corinthians. Paul discusses the role of the Spirit in personal lives, community formation, and worship, among other aspects of Christian living. Paul’s teaching about the Holy Spirit in 1 Corinthians cannot be understood apart from the situation of the congregation in Corinth. It is not possible to address every issue related to the Holy Spirit in an essay of this length. However, Paul highlights and sometimes elaborates on different aspects of the ministry and function of the Holy Spirit among believers in several passages. Therefore, the approach in this essay is to look at some of the passages and see how much they foster the understanding of the Holy Spirit’s work in 1 Corinthians.